Analisis Kepatuhan Wajib Pajak Orang Pribadi Berdasarkan Gender, Jenis Pekerjaan, dan Tingkat Pendidikan - Hana Salsabila; Desi Handayani; Randy Heriyanto (Akuntansi dan Manajemen, 2022)
In contrast to previous research which discussed the factors that influence taxpayer compliance, this study will measure how differences in the level of individual taxpayer compliance are based on the factors that influence it. This difference is measured using the variables gender, type of work and educational level of taxpayers registered at KPP Pratama Padang Satu. The data collection method used in this study was a questionnaire. The population of this study is taxpayers registered at KPP Pratama Padang Satu, with 100 respondents. While the method of data analysis and hypothesis testing used independent t-test and Kruskal Wallis. The result of this study is proves that there is no difference between female and male taxpayers in fulfilling individual taxpayer compliance. This study proves that there are differences between employee and non-employee taxpayers in fulfilling individual taxpayer compliance. This study proves that there are differences between taxpayers with high school education, Associate's degree, Bachelor degree, and Masters education levels in fulfilling individual taxpayer compliance. This research is expected to make a practical contribution to the government to provide socialization to taxpayers to be more obedient in paying taxes.